Time-Dependent Effect of Anthracycline-Based Chemotherapy on Central Arterial Stiffness: A Systematic Review and Meta-Analysis - Schneider, Caroline; González-Jaramillo, Nathalia; Marcin, Thimo; Campbell, Kristin L.; Suter, Thomas; Bano, Arjola; Wilhelm, Matthias; Eser, Prisca (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims Anthracycline-based chemotherapy (Anth-bc) has been proposed to increase arterial stiffness, however, the time-dependency of these effects remain unclear. This systematic review and meta-analysis aimed to investigate the time-dependent effect of Anth-bc on markers of central aortic stiffness, namely aortic distensibility (AD) and pulse-wave-velocity (PWV) in cancer patients. Methods An extensive literature search without language restrictions was performed to identify all studies presenting longitudinal data on the effect of Anth-bc on either AD and/or central PWV in cancer patients of all ages. An inverse-variance weighted random-effect model was performed with differences from before to after chemotherapy, as well as for short vs. mid-term effects. Results Of 2130 articles identified, 9 observational studies with a total of 535 patients (mean age 52±11; 73% women) were included, of which four studies measured AD and seven PWV. Short-term (2-4 months), there was a clinically meaningful increase in arterial stiffness, namely an increase in PWV of 2.05 m/s (95% CI 0.68 to 3.43) and a decrease in AD (albeit non-significant) of -1.49 mmHg-1 (-3.25 to 0.27) but a smaller effect was observed mid-term (6-12 months) for PWV of 0.88 m/s (-0.25 to 2.02) and AD of -0.37 mmHg-1 (-1.13 to 0.39). There was considerable heterogeneity among the studies. Conclusions Results from this analysis suggest that in the short-term, Anth-bc increases arterial stiffness, but that these changes may partly be reversible after therapy termination. Future studies need to elucidate the long-term consequences of Anth-bc on arterial stiffness, by performing repeated follow-up measurements after Anth-bc termination.